2021
DOI: 10.1073/pnas.2102721118
|View full text |Cite
|
Sign up to set email alerts
|

Learning hidden elasticity with deep neural networks

Abstract: Elastography is an imaging technique to reconstruct elasticity distributions of heterogeneous objects. Since cancerous tissues are stiffer than healthy ones, for decades, elastography has been applied to medical imaging for noninvasive cancer diagnosis. Although the conventional strain-based elastography has been deployed on ultrasound diagnostic-imaging devices, the results are prone to inaccuracies. Model-based elastography, which reconstructs elasticity distributions by solving an inverse problem in elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Moreover, it would allow us to create descriptive computational models to investigate cell biomechanics, including the potential to estimate cell elasticity and identify loading modalities that lead to cell softening and stiffening. 59 Taken together, these experimental and computational approaches would inform our understanding of AF cell mechanobiology and potentially identify the initiation and development of disc degeneration. Future work will investigate the response of human AF cells within the device as well as 3D cell-laden constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would allow us to create descriptive computational models to investigate cell biomechanics, including the potential to estimate cell elasticity and identify loading modalities that lead to cell softening and stiffening. 59 Taken together, these experimental and computational approaches would inform our understanding of AF cell mechanobiology and potentially identify the initiation and development of disc degeneration. Future work will investigate the response of human AF cells within the device as well as 3D cell-laden constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in laser-based ultrasonic testing has led to the emergence of dense spatiotemporal datasets which along with suitable data analytic solutions may lead to better understanding of the mechanics of complex materials and components. This includes learning of distributed mechanical properties from test data which is of interest in a wide spectrum of applications from medical diagnosis to additive manufacturing [1,2,3,4,5,6,7]. This work makes use of recent progress in deep learning [8,9] germane to direct and inverse problems in partial differential equations [10,11,12,13] to develop a systematic full-field inversion framework to recover the profile of pertinent physical quantities in layered components from laser ultrasonic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In the model-free data-driven realm, recent works (Leygue et al, 2018;Dalémat et al, 2019;Cameron and Tasan, 2021) have demonstrated estimation of stress fields from full-field displacement data. In the model-based realm, physics-informed neural networks (PINNs) and their variations have shown promising results -by first learning the forward solution, i.e., displacement fields, to the mechanical boundary boundary value problem as a function of the material parameters and then estimating the unknown parameters via gradient-based optimization (Huang et al, 2020;Tartakovsky et al, 2018;Haghighat et al, 2020;Chen and Gu, 2021). However, all the aforementioned methods (including FEMU, VFM, and PINNs) are limited to a priori assumed constitutive models (e.g., with known deformation modes) with only a few unknown parameters.…”
Section: Introductionmentioning
confidence: 99%